Analisis Kaidah Tafsir dalam Menafsirkan Ayat-Ayat Sains Study Tafsir Al-Manar - Khafizuddin, M. Fuad; Akbar, Ali; Ismail, Hidayatullah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
In an effort to understand the relationship between Islamic teachings and the development of modern science, the analysis of the interpretive principles applied in Tafsir Al-Manar by Muhammad Abduh and Muhammad Rasyid Ridha becomes highly relevant. This study aims to analyze the interpretive principles employed in Tafsir Al-Manar, particularly in the context of scientific verses. The method used in this paper is library research, which involves collecting data from various relevant literatures. The results of the analysis show that Tafsir Al-Manar applies profound and relevant interpretive principles by connecting the verses of the Qur'an with Hadith, utilizing a rational approach, and emphasizing social, moral, and historical contexts. This tafsir is distinguished from others by its balanced interpretation method (mustawah), explaining the meanings of verses in detail without excessive elaboration. By linking revelation with modern knowledge, Tafsir Al-Manar serves as a bridge between Islamic tradition and contemporary challenges. With its innovative approach, Tafsir Al-Manar demonstrates that the Qur'an can be understood in the context of modern science, making it a source of inspiration for Muslims in facing the challenges of the times.